Weed competition in a maize-bean intercropping system - Ramalho, Magno A. P.; Cruz, José Carlos; Passini, Telma (Pesquisa Agropecuaria Brasileira, 2014)
Weed competition in both monoculture and intercropping plantings of maize (Zea mays L.) and beans (Phaseolus vulgaris L.) was evaluated for three years in experiments at the National Maize and Sorghun Research Center (CNPMS/EMBRAPA) at Sete Lagoas, Minas Gerais, Brazil. The productivity of maize was not significantly affected by the cropping system but the bean yield was reduced 64% in the intercropping system. Considering that the maize production was equal in both systems, the intercropping was more productive than either monoculture. Weed competition maize affected productivity more in the monoculture system than in the consortium with beans, whereas, weed competition with the bean crop was greater in the consortium with maize than in the monoculture planting, independent of the intercropping system: beans planted in the row with maize and beans planted between the rows of maize. The period of greatest weed competition was the same for both the monoculture and intercropping occurring between fifteen and 50 days after planting.